Masyarakat Multikultural Perspektif Indonesia: Mengkaji Ulang Teori Multikultural Bikhu Parekh - Moch Iqbal (Indonesian Journal of Social Science Education (IJSSE), 2023)
The purpose of this paper is to review Bikhu Parekh's thoughts on the categorization of multiculturalism. Using the literature review method, namely by reviewing available library sources, both off-line and on-line sources. The results of this study resulted in the need to review the multiculturalism categorization of Bikhu Parekh which is often used in multiculturalism studies in Indonesia. First, the categorization of Parek monks is no longer relevant in the current context, both globally and locally. Second, the Multicultural Bikhu Parekh tends to be Western oriented, tends to ignore multicultural forms in various parts of the world. Third, multiculturalism in the Indonesian context has its own characteristics and uniqueness, different from the multicultural characteristics that exist in the West which are the fulcrum of the multicultural categorization of Bikhu Parekh. Multiculturalism in Indonesia is formed naturally. From the beginning, Indonesia, which was formerly known as the Dutch East Indies, was a pluralistic, multi-ethnic society which later formed Indonesia.